Echiniscidae (Heterotardigrada) of South Africa - Gąsiorek, Piotr; Vončina, Katarzyna; Bochnak, Marcin; Surmacz, Bartłomiej; Morek, Witold; Michalczyk, Łukasz (Zootaxa, 2022)
The first publications on the Afrotropical tardigrade fauna date back to the beginning of the 20th century. However, the knowledge on the faunal composition, diversity and evolution of African tardigrades, including the speciose family Echiniscidae, is still fragmentary. Here, we present an extensive systematic, biogeographic, and ecological survey of echiniscid fauna of the southernmost part of the Afrotropical realm. Sampling was conducted in several biodiverse regions of South Africa: South African Woodlands and Savannahs, Cape evergreen sclerophyllous forests and scrubs, semi-desert Karoo, and the Afromontane Drakensberg and Swartberg ranges. The application of tools of integrative taxonomy allowed for the identification of 36 distinct echiniscid species grouped in five genera. Among these, as many as 19 species representing three genera, are described here as new to science: Echiniscus attenboroughi sp. nov., E. capensis sp. nov., E. dentatus sp. nov., E. draconis sp. nov., E. gracilis sp. nov., E. imitans sp. nov., E. intricatus sp. nov., E. irroratus sp. nov., E. latruncularis sp. nov., E. oreas sp. nov., E. regularis sp. nov., E. scabrocirrosus sp. nov., E. setaceus sp. nov., E. similaris sp. nov., E. tetraspinosus sp. nov., Hypechiniscus africanus sp. nov. (the exarmatus group), Pseudechiniscus (Pseudechiniscus) aquatilis sp. nov., P. (P.) linnaei sp. nov., and P. (Meridioniscus) wallacei sp. nov. Moreover, E. longispinosus Murray, 1907 and E. perarmatus Murray, 1907 are formally re-described and their neotypes are established. Amendments to outdated descriptions of E. africanus Murray, 1907 and E. crassispinosus Murray, 1907 are also provided. Species descriptions and redescriptions contain detailed data on ecological preferences of species, their ontogenetic variability, sex ratios in gonochoristic/dioecious populations (males are recorded in African Echiniscus spp. for the first time), and, finally, on their phylogenetic relationships. The study reveals a diverse echiniscid assemblage, dominated by Echiniscus, that overlaps with the hotspots of Cape Floristic Region, Succulent Karoo, and Maputaland-Pondoland-Albany. According to our phylogenetic analyses, the great majority of South African Echiniscus species are endemics and they evolved from several species that colonised the region after the genus had originated (in contrast to earlier hypotheses, our work suggests that Echiniscus has the Laurasian rather than the Gondwanan origin). The remaining echiniscids found in South Africa represent pantropical or cosmopolitan species.